Estimation of the Spectral Composition of the Signal by the Antenna Composed of Multiple Satellites. (2015) - Vinogradov, S.V.; Zhuravlev, V.M.; Fundaev, S.V.
Abstract: The problem of calculation of spectral density of wave process are represented in this work on base of data from antenna array with variable conﬁguration. This antenna array is an aggregate sensing elements moving in space with constant velocities related to laboratory frame system and related one another. The new way of transformation an initial data set obviated difficulties with inhomogeneous Dopler's shifts in antenna nodes are suggested.